Successful Treatment of Plaque Psoriasis with Allogeneic Gingival Mesenchymal Stem Cells: A Case Study - Sebo Gene Wang; Nicholas C. Hsu; Sebo Michelle Wang; Fu Nan Wang (Hindawi Limited, 2020)
Plaque psoriasis is the most common type of psoriasis that manifests as red scaly patches with white scales affecting body areas including scalp, elbows, knees, trunk, and buttocks. Although many treatment options are available including novel biologics, no cure is available. Mesenchymal stem cells (MSCs) have been safely used to treat a variety of human diseases. Allogeneic MSCs possess unique characteristics including hypoimmunogenicity, immunomodulatory, and anti-inflammatory properties, and they are currently being explored for potential therapeutic use for many systemic inflammatory diseases. The human gingival tissue is an easily accessible and obtainable source for the isolation of MSCs. MSCs from adult human gingiva are of fetal-like phenotype, multipotent, and easy to isolate and expand in vitro. Herein, we report a case of a 19-year-old man with a 5-year history of severe plaque psoriasis refractory to multiple topical and systemic therapies who was treated with allogeneic human gingival MSCs. Complete regression was achieved after 5 infusions with no adverse reaction occurred. The patient has been followed for three years and has remained disease free.